The diversity, distribution and conservation status of the tree‐cavity‐nesting birds of the world - van der Hoek, Yntze (2017)
Aim: Globally, many bird species nest in tree cavities that are either excavated or formed through decay or damage processes. We assembled an overview of all tree-cavity nesters (excavators and non-excavators) in the world, analysed their geographic distribution and listed the conservation status of all species. Location: This is a global analysis of species from every continent except for Antarctica where the lack of trees precludes the occurrence of this group. Methods: We reviewed the online version of the Handbook of the Birds of the World Alive, http://www.hbw.com/, and primary literature for species known to nest in tree cavities, with tree cavities defined as holes that a bird can enter such that it is not visible from the outside. We classified species by nester type (excavator or non-excavator, and obligate or facultative where possible), conservation threat status and zoogeographic region, and tested for statistical differences in species distributions across realms using chi-square tests. Results: At least 1878 species (18.1% of all bird species in the world) nest in tree cavities, of which we considered 355 to be primary excavators, 126 facultative excavators and 1357 non-excavators (we were unable to classify nesting type for 40 species). At least 338 species use cavities created by woodpeckers (Picidae), excluding reuse by woodpeckers themselves. About 13% (249 species) of tree-cavity nesters experience major threats (i.e., status of vulnerable, endangered or critically endangered). The highest richness of tree-cavity nesters is found in the Neotropical (678 species) and Oriental (453) regions, and the highest proportion of threatened species in Australasia (17%). Main conclusion: Maintenance of a continual supply of cavities, a process in which woodpeckers and the processes of decay play critical roles, is a global conservation priority as tree cavities provide important nesting sites for many bird species.